Problems of social polarization in modern cities - G. P. Podolian (Ukrainian Cultural Studies, 2019)
The article is devoted to the analysis of complex processes of social polarization as an integral feature of the modern life of big cities, which manifests itself in the confrontation of the elite and disadvantaged segments of the urban population. It is emphasized on the spectrum of the main causes, characteristic features that have determined the rise of these trends in modern cities around the world. Emphasis is placed on the devastating impact of social polarization on the social foundations of communication, interaction and integration of different segments of the population within one city. By comparing the practice of the existence of cities in classical cultures with the modern experience of func- tioning of large cities, the main causes of such a situation are analyzed. The universal include: globalization, NTP and urbanization. Other, not less significant, include economic ones: formation of world interdependence, first of all, in economic activity, becoming of post-industrial production with appropriate type, practices and values, increase of level and possibilities of technological transformations, existence of competitive ways of production, uneven development of production, increasing dependence of many economies from tourism development, poverty growth and the emergence of megabidonville, international labor migration rates; social: the emergence and subsequent dominance of a new type of intellectual elite focused on global communication space (cyberspace), the formation of "closed spaces" for different layers within the same city, breaking a complex network of relationships and interaction between different layers, leaving the solution of local problems to solve poor people, displacing the poorer from the best places of urban infrastructure, rigid polarization and segregation between different layers; cultural: the presence in the vast majority of large cities of ethnic groups, races and peoples; worldviews: fear, uncertainty in the future, vulnerability of the social situation in the conditions of "current modernity". An analysis of the dynamic nature of urban life has allowed to identify the main drivers of social polarization – myxophobia and myxophilia and to determine their negative influences and positive possibilities of maintaining social communication, interaction, agreements, exchanges in the context of the functioning of the big city of the modern global world.